Chromatin Protamination and Catsper Expression in Spermatozoa Predict Clinical Outcomes after Assisted Reproduction Programs. Issue 1 (December 2017) - Marchiani, S.; Tamburrino, L.; Benini, F.; Fanfani, L.; Dolce, R.; Rastrelli, G.; Maggi, M.; Pellegrini, S.; Baldi, E.
Abstract Identification of parameters predicting assisted reproductive technologies (ARTs) success is a major goal of research in reproduction. Quality of gametes is essential to achieve good quality embryos and increase the success of ARTs. We evaluated two sperm parameters, chromatin maturity and expression of the sperm specific calcium channel CATSPER, in relation to ART outcomes in 206 couples undergoing ARTs. Chromatin maturity was evaluated by Chromomycin A3 (CMA3) for protamination and Aniline Blue (AB) for histone persistence and CATSPER expression by a flow cytometric method. CMA3 positivity and CATSPER expression significantly predicted the attainment of good quality embryos with an OR of 6.6 and 14.3 respectively, whereas AB staining was correlated with fertilization rate. In the subgroup of couples with women ≤35 years, CATSPER also predicted achievement of clinical pregnancy (OR = 4.4). Including CMA3, CATSPER and other parameters affecting ART outcomes (female age, female factor and number of MII oocytes), a model that resulted able to predict good embryo quality with high accuracy was developed. CMA3 staining and CATSPER expression may be considered two applicable tools to predict ART success and useful for couple counseling. This is the first study demonstrating a role of CATSPER expression in embryo development after ARTs programs.